Fontes de espermina e atividade antioxidante in vivo - Cecilia Muller Bandeira (2011)
This work aimed to evaluate the antioxidant effect of polyamine spermine in vivo. Was investigated the presence of this amine in foods and by-products (liver, testis, passion fruit peel and corn) as a source for extraction and subsequent use in animal diets. Different types of maize were analyzed to verify the potential of spermine as a source for human diet too. Using colunm chromatography, spermine was extracted from liver extract. Pilot experiment was conducted with a small number of mice to adequacy of treatments and after sixty animals were randomly assigned to six treatments, which were given in two doses of spermine (27 and 54 mg / kg) during two periods of time (six and twelve days) and the respective control groups. The results were analyzed with respect to effects on quality and oxidation in meat, simulating the analysis performed in meat from farm animals intended for human consumption and action on the endogenous antioxidation system of rats. The spermine promoted oxidation of meat, verified by increased formation ofmalonaldehyde and conjugated dienes. There was no difference between the groups that received spermine and controls in relation to food efficiency ratio and pH of the meat. Spermine concentrations were higher in meat from animals treated for six days, compared to other groups, however, there was no influence of the doses used. Animals treated for twelve days had darker and yellow meat, with respect tothe observed color parameters L* and b*. The effect of spermine administration on the endogenous enzymatic antioxidant system showed satisfactory results, due to increased activity of the enzymes superoxide dismutase and catalase in treated groups compared to control groups, suggesting their activation under the conditions evaluated, which contributes to the defense the body against damage from oxidationcaused by reactive oxygen species. The treatments showed increased protein oxidation in the groups receiving spermine compared to control groups. No treatment effect was observed on the enzyme concentrations of indicators of oxidative stress and nitric oxide. Thus, in some situations there was the antioxidant effect of spermine in vivo.